2019
DOI: 10.1055/s-0039-1693286
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Evaluating the Etiologic Spectrum in Patients with Dysphagia in Coastal Odisha Using Clinical Features and Endoscopy

Abstract: Background There is scarcity of data on the etiological spectrum of dysphagia from India. The study was conducted to determine the etiological spectrum of dysphagia in coastal Odisha. Materials and MethodsConsecutive patients presenting with dysphagia to the gastroenterology outpatient department in 2017 were studied. Patients were evaluated with meticulous history, clinical examination, esophagogastroduodenoscopy, and chest X-ray. Barium study and endoscopic biopsy were done when necessary. Results Of 216 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[ 1 13 14 15 26 27 28 ] Among 28 patients with esophageal stricture, only 4 (14.3%) had esophageal stricture either peptic or secondary to active esophagitis, and this number is far less than that reported from Panigrahi et al . [ 29 ] stating corrosive stricture and Western data stating gastro-esophageal reflux disease (GERD) as the main etiologies of dysphagia. [ 12 30 ] These trends clearly indicate the esophageal growth as one of the most common reasons of dysphagia in our settings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 13 14 15 26 27 28 ] Among 28 patients with esophageal stricture, only 4 (14.3%) had esophageal stricture either peptic or secondary to active esophagitis, and this number is far less than that reported from Panigrahi et al . [ 29 ] stating corrosive stricture and Western data stating gastro-esophageal reflux disease (GERD) as the main etiologies of dysphagia. [ 12 30 ] These trends clearly indicate the esophageal growth as one of the most common reasons of dysphagia in our settings.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 216 consecutive patients admitted to the gastroenterology outpatient department with a history of dysphagia were included in the study. Benign strictures were diagnosed in 31.48% (corrosive injury in 70.59%, peptic stricture in 11.76%, postoperative strictures in 5.88%) and esophageal carcinomas in 23.62% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is a frequent complaint of patients presenting in GI clinics [7][8][9][10]. The causes of dysphagia of esophageal origin that are identified commonly are benign and malignant strictures of esophagus, reflux esophagitis, Schatzki's ring, compression occurring externally from a malignancy, disorders of motility, scleroderma and achalasia [11][12][13][14][15][16]. In some population-based studies, the rates of prevalence of dysphagia have been reported to be 17-25% with a peak in symptoms at the age of 40-49 years for both gender [17,18].…”
Section: Discussionmentioning
confidence: 99%